Dissolution of basalts and peridotite in seawater, in the presence of ligands, and CO2: Implications for mineral sequestration of carbon dioxide - Wolff-Boenisch, Domenik; Wenau, S.; Gislason, S.; Oelkers, E. (Pergamon-Elsevier Science Ltd, 2011)
Steady-state silica release rates (rSi) from basaltic glass and crystalline basalt of similar chemical composition as well as dunitic peridotite have been determined in far-from-equilibrium dissolution experiments at 25 °C and pH 3.6 in (a) artificial seawater solutions under 4 bar pCO2, (b) varying ionic strength solutions, including acidified natural seawater, (c) acidified natural seawater of varying fluoride concentrations, and (d) acidified natural seawater of varying dissolved organic carbon concentrations. Glassy and crystalline basalts exhibit similar rSi in solutions of varying ionic strength and cation concentrations. Rates of all solids are found to increase by 0.3–0.5 log units in the presence of a pCO2 of 4 bar compared to CO2 pressure of the atmosphere. At atmospheric CO2 pressure, basaltic glass dissolution rates were most increased by the addition of fluoride to solution whereas crystalline basalt rates were most enhanced by the addition of organic ligands. In contrast, peridotite does not display any significant ligand-promoting effect, either in the presence of fluoride or organic acids. Most significantly, Si release rates from the basalts are found to be not more than 0.6 log units slower than corresponding rates of the peridotite at all conditions considered in this study. This difference becomes negligible in seawater suggesting that for the purposes of in-situ mineral sequestration, CO2-charged seawater injected into basalt might be nearly as efficient as injection into peridotite.